An Investigation of Social Support Levels in Mothers of Children with Cerebral Palsy in Early Childhood - Pelin Piştav Akmeşe; Nilay Kayhan (Sakarya University, 2016)
Cerebral Palsy (CP) is a common developmental disability. CP is primarily a disorder of movement and posture. Associated deficits are present in large majority; mental retardation, visual impairement, hearing impairment, epilepsy, speech and language disorders. In this study, it is aimed to investigate the perception of social support levels of the mothers of the children with CP in early childhood period in terms of the variables regarding the sex of the children, the level of the disability, the frequency of talking to the relatives, neighbors or friends on the phone or face to face, having a house guest, going outside for the job and carrying the responsibility of the child. The study was conducted with 90 children with CP, 36 female and 54 male, and their mothers. First, the children were evaluated according to Gross Motor Function Classification System (GMFCS) and their clinical types, then the Social Support Scale (SSS) was applied to the mothers. The data obtained were analyzed with t-test and One Way ANOVA by using the SPSS 21.0 program. p<.05 was accepted as statistically significant. When the results of this study, there is statistically significant in terms of seeing the relatives, neighbors or friends face to face, frequency of having a house guest, frequency of going go out for job purpose except for working, and caregiver burden of the children. It is thought that the findings obtained in this study will contribute to supporting the mothers who caregiver burden of the children in rehabilitation and education in different areas.